Translanguaging and minoritized language maintenance: lessons from Indonesia - Margana,; Rasman, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Translanguaging has been considered as an effective pedagogical approach to foster multilingualism. Previous studies have suggested further that teaching English through pedagogical translanguaging can increase participation of language-minoritized students and thus, promote minoritized language maintenance. However, it remains unclear as to what extent the assumed transformative power of translanguaging allows students to challenge prevailing monolingual ideologies that are gradually pushing minoritized language use to the periphery of society. There is growing evidence that promoting translanguaging practices to language-minoritized students can inadvertently contribute to their language shift from minoritized to majoritized languages (i.e., English and national languages). To maintain and extend this discussion, this article reports on a case study investigating the extent to which translanguaging practices in a tertiary-level EFL class in Indonesia contributes to the efforts to reverse language shift from Javanese to Indonesian and English. The data were drawn from audio-recorded classroom interactions, artefacts of student work and follow-up semi-structured interviews. The findings suggest that translanguaging pedagogy can support minoritized language maintenance only when language inequalities and language hierarchies are transgressed. Furthermore, the effectiveness of translanguaging in maintaining Javanese seemingly relies on whether students have enough proficiency in the Javanese language. Otherwise, the endorsement of translanguaging in this polity may be perceived as an opportunity to practice more dominant languages.